Toeti Heraty: penyair feminis Indonesia (1967-2000) - Safika Salsabila Dwiningtyas; Nur'aeni Marta; Sri Martini (Historiography: Journal of Indonesian History and Education, 2023)
This study aims to explain Toeti Heraty's biography as a feminist poet and also to describe her works with the theme of feminism both in the form of poetry and lyrical prose in the period 1967-2000. The method used is the historical method which consists of 5 steps namely identify the topic, heuristics, verification, interpretation, and historiography. The results of the study state that Toeti's initial contribution to the world of literature began when his poetry was published by Horison Magazine in 1967. In 1974 Toeti published a book of his poems entitled Sajak-Sajak 33. In 1982, Toeti published his second poetry anthology entitled Mimpi dan Pretensi. Toeti published his third anthology of poetry in 1995 entitled Nostalgi=Transendensi. Some of Toeti's poems carry the theme of feminism and the image of women in society. This theme is the hallmark of Toeti's poems. Â The figure of speech that Toeti uses in her poetry is dominated by the irony of life.Penelitian ini bertujuan untuk menjelaskan biografi Toeti Heraty sebagai seorang penyair feminis dan juga mendeskripsikan karya-karyanya yang bertemakan feminisme baik dalam bentuk sajak ataupun prosa lirik dalam rentang tahun 1967-2000. Metode yang digunakan adalah metode sejarah yang terdiri dari 5 tahapan yaitu pemilihan topik, heuristik, verifikasi, interpretasi, dan historiografi. Hasil penelitian menyatakan bahwa kiprah awal Toeti dalam dunia sastra dimulai ketika sajaknya diterbitkan oleh Majalah Horison pada tahun 1967. Pada tahun 1974 Toeti membukukan sajak-sajak yang diciptakannya dan diberi judul Sajak-Sajak 33. Tahun 1982, Toeti menerbitkan antologi puisi keduanya yang diberi judul Mimpi dan Pretensi. Toeti menerbitkan antologi puisinya yang ketiga pada tahun 1995 berjudul Nostalgi=Transendensi. Beberapa sajak yang Toeti buat mengusung tema feminisme dan citra perempuan dalam masyarakat. Tema tersebut menjadi ciri khas dari sajak-sajak ciptaan Toeti. Gaya bahasa yang Toeti gunakan dalam puisinya didominasi oleh ironi kehidupan.